Perceptual Learning Produces Perceptual Objects. - Wenger, Michael J.; Rhoten, Stephanie E. (Journal of Experimental Psychology. Learning, Memory & Cognition, 2020)
In their seminal study of chess expertise, Simon and Chase (Chase & Simon, 1973; Simon & Chase, 1973) proposed that perceptual learning was a necessary component of skill acquisition. In their view, acquisition of skill results from the strategic use of learning at multiple levels to adaptively overcome inherent limitations. The knowledge acquired by way of perceptual learning that supported increasingly sophisticated perceptual discrimination processes, according to Simon and Chase, was referred to as a chunk. The chunk was conceptualized as a meaningful complex set of features that abstracted the notion of a perceptual object. Simon and Chase further suggested that meaningful combinations of chunks could be combined to form configurations (Simon & Chase, 1973, p. 399). The present study addresses this idea by framing the notion of a chunk in terms of two formal metatheories, one that addresses representation (Ashby & Townsend, 1986) and one that addresses processing (Townsend & Nozawa, 1995), and tests the prediction that perceptual learning produces organized perceptual objects (chunks). Two experiments combine behavioral and electroencephelographic (EEG) measures to show that perceptual learning produces (a) a shift from perceptual independence and separability to violations of separability, and (b) shifts from limited-capacity serial processing to supercapacity parallel processing. The evidence from both experiments is strong and consistent: perceptual learning does indeed induce chunking—the production of perceptual objects, and the foundation of perceptual expertise.